Unpacking informal contractual relationships: psychological contracts established by Australian business academics - O'Neill, Grant; Krivokapic-Skoko, B.; Dowell, D. (Irish Academy of Management, 2010)
This paper addresses the findings from exploratory research on the content of psychological contracts formed by business academics within an Australian university. The research used a sequential multi-method research design, where focus groups were initially conducted to elicit insights into the content of the academics’ psychological contracts. A cross-sectional survey was then administered and exploratory factor analysis of the data collected was undertaken. Cluster analysis was used to further examine perceived employer and employee obligations within a university context, and it proved useful as a means of deepening understanding of academics’ psychological contracts, variation among them, and their possible workplace effects. The research identified the existence of quite divergent expectations, interests, motivations and levels of commitment by the academics to the university. It is argued that sensitivity to such variations, and appropriate tailoring of management initiatives and messages, is important if the university is to achieve its goals.